2021
DOI: 10.1097/fjc.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue in Vascular Function: Does Locally Synthesized Angiotensinogen Play a Role?

Abstract: In recent years, perivascular adipose tissue (PVAT) research has gained special attention in an effort to understand its involvement in vascular function. PVAT is recognized as an important endocrine organ that secretes procontractile and anticontractile factors, including components of the renin-angiotensin-aldosterone system, particularly angiotensinogen (AGT). This review critically addresses the occurrence of AGT in PVAT, its release into the blood stream, and its contribution to the generation and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…Apparently, therefore, despite local AGT expression, the actual AGT protein at these extrahepatic sites is liver derived. Given these findings, which coincide with observations in transgenic animals genetically lacking kidney or adipose tissue AGT, 20,[49][50][51][52] currently, mechanisms are being investigated that might explain AGT uptake from blood. Here, an important newly identified candidate is the megalin receptor.…”
Section: Highlightssupporting
confidence: 66%
“…Apparently, therefore, despite local AGT expression, the actual AGT protein at these extrahepatic sites is liver derived. Given these findings, which coincide with observations in transgenic animals genetically lacking kidney or adipose tissue AGT, 20,[49][50][51][52] currently, mechanisms are being investigated that might explain AGT uptake from blood. Here, an important newly identified candidate is the megalin receptor.…”
Section: Highlightssupporting
confidence: 66%
“…This confirms that also in mice, eWAT angiotensinogen is predominantly derived from the liver, at least under normal circumstances. 25 Fludrocortisone increased blood pressure similarly in hepatocyte angiotensinogen‐deficient and control mice, but was unable to upregulate plasma angiotensinogen and even reduced plasma angiotensinogen concentrations in control mice, in spite of upregulated Agt mRNA and angiotensinogen protein abundance in eWAT in both strains. In hepatocyte angiotensinogen‐deficient mice, the increase in eWAT after fludrocortisone was of similar magnitude as that in the siRNA‐treated rats.…”
Section: Discussionmentioning
confidence: 97%
“…Not all human adipokines have been identified, but the current literature has revealed that the surface adipose tissue secretes more than 600 factors or proteins involving many processes of human pathophysiology[ 130 ]. There are many types of adipokines, including cytokines[ 22 ], fibrinolysin[ 44 ], complement and related proteins[ 49 ], enzymes[ 121 ], lipid transport systems[ 116 ], endocannabinoids[ 131 ], and angiotensinogen[ 132 ] (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%